THE INFLUENCE OF ENTREPRENEURIAL LITERACY AND DIGITAL LITERACY ON BUSINESS SUCCESS (A Study on SMEs Assisted by the Department of Cooperatives in Biringere Village, North Sinjai District, Sinjai Regency) - Muhammad Taufik Hidayat; Anwar Ramli; Muhammad Hasan (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Abstract This research intends to examine the influence of entrepreneurial literacy as well as digital literacy on company success (Study on MSME Assisted by the Cooperative Office in Biringere Village, North Sinjai District, Sinjai Regency). The t-test analysis indicates that the entrepreneurial literacy and digital literacy variables have a significant influence on Business Success, thereby confirming the hypothesis. The F-test results indicating that the independent variables have a significant simultaneous influence on the dependent variable. The correlation coefficient analysis (r) yielded a value of 0.793 or 79.3 percent, suggesting a positive relationship where higher entrepreneurial literacy and digital literacy are associated with greater Business Success. The analysis of the coefficient of determination (R²) indicates that entrepreneurial literacy accounts for 55.5% of the influence on Business Success, while the remaining 44.5% is attributed to other factors. The digital literacy coefficient value is 0.449, or 44.9%, indicating that digital literacy contributes 44.9% to the impact on Business Success, while the remaining 55.1% is impacted by external factors.